IMPLEMENTASI KODE ETIK JURNALISTIK PADA FOTO JURNALISTIK DALAM RUBRIK HUKUM KRIMINAL DI PORTAL BERITA GoRiau.com - Nofita Tri Gamala; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Technological advances that teaches people to obtain information quickly, cheaply and efficiently and also supported by holding of the Press Oublishing Business License (SIUPP), making the height popping new news portal. So that the number of photos uploaded increasingly uncontrollable and disturbing the public. However, on the other hand, the press has a Journalistic Code of Ethics which is the main reference at the same spirit of the press to behave. This study aims to investigate the implementation of journalism code of ethics in journalism photo of Hukum Kriminal Rubric at GoRiau.com News Portal.This study uses descriptive analysis with qualitative approach. Research conducted at GoRiau.com News Portal, Surya Kartama Agung street 4Ath Pekanbaru. Through purposive sampling technique, the number of subjects in this study as many as seven (7) members. Technical analysis of the data using interactive data analysis model of Miles and Huberman.The results showed that; first, the implementation of Journalism code of ethics by GoRiau.com news portal not maximized. Proved by the number of uploads found journalism photo is considered quite sadistic, visible from the elements of blood on the photo. Then lewd photos where the photograph shows the lower part of the body that opens up almost to the vital organs, and does not follow the presumption of innocence. The portal is also inconsistent in presenting the news. Furthermore, the system boosts straight news reporters increasingly raising the level of negligence. Because no matter what, the press has a social responsibility to the government and society. Second, conditions Journalistic Code violations that do not have the sanction further debilitates the Journalistic Code of Ethics itself. Sanctions only found in the Press Law. Such circumstances should mobilize governments and communities to be more intelligent in responding to this phenomenon. Because in fact, social responsibility also embrace the government and the community to keep the continuity of GoRiau.com New Portal not to deviate from the rules applicable thus causing things that are not desirable.Keyword: The implementation of journalism code of ethics, journalism photo, Hukum Kriminal Rubric, GoRiau.com News Portal